PEMAHAMAN GENDER DALAM PERSPEKTIF HADIS - Barella, Yusawinur; Yahya, Muhammad; Asse, Ambo (Holistic al-Hadis, 2023)
This research aims to explore relevant hadiths related to the understanding of gender and analyze the clarity of the hadiths' chain of narration. The research method used is takhrij, which involves the analysis of hadiths related to gender issues and the study of relevant literature in the context of Islamic scholarship and gender studies. Moreover, it employs I'tibar sanad, which seeks to find stronger narration chains than other chains. The data analysis is carried out through critically examining the content (matn), a method commonly used in hadith research to assess the accuracy and reliability of hadiths based on their content. The research results show that hadiths guide the role and position of women in Islam, but there are often variations and different interpretations. This research also highlights the importance of evaluating and understanding the clarity of the hadiths' chain of narration to understand religious teachings accurately in the context of gender.